Cerebral Microbleed Automatic Detection System Based on the “Deep Learning” - Fan, Pingping; Shan, Wei; Yang, Huajun; Zheng, Yu; Wu, Zhenzhou; Chan, Shang Wei; Wang, Qun; Gao, Peiyi; Liu, Yaou; He, Kunlun; Sui, Binbin (Frontiers in Medicine, 2022)
Objective: To validate the reliability and efficiency of clinical diagnosis in practice based on a well-established system for the automatic segmentation of cerebral microbleeds (CMBs). Method: This is a retrospective study is based on MRI-SWI datasets from 1615 patients (median age, 56 years; 1115 males, 500 females) obtained between September 2018 and September 2019. All patients had been diagnosed with cerebral small vessel disease (CSVD) with clear cerebral microbleeds (CMBs) on MRI-SWI. The patients were divided into training, and validation cohorts of 1,285 and 330 patients respectively, and another 30 patients were used for internal testing. The model training and validation data were labeled layer by layer and rechecked by two neuroradiologists with 15 years of work experience. Afterward, a three-dimensional convolutional neural network (CNN) was applied to the MRI data from the training and validation cohorts to construct a deep learning system (DLS) that was tested with the 72 patients, independent of the aforementioned MRI cohort. The DLS tool was used as a segmentation program for these 72 patients. These results were evaluated and revised by 5 neuroradiologists and subjected to an output analysis divided into missed label, incorrect label and correct label. The interneuroradiologists DLS agreement rate, which was assessed using the interrater agreement kappas test, was used for the quality analysis. Results: In the detection and segmentation of the CMBs, the DLS achieved a Dice coefficient of 0.72. In evaluation of the independent clinical data, the neuroradiologists reported that more than 90% of the lesions were directly detected, and less than 10% of lesions were incorrectly labeled or the label was missed by our DLS. The kappa value for interneuroradiologist DLS agreement reached 0.79 on average. Conclusions: Based on the results, the automatic detection and segmentation of CMBs are feasible. The proposed well-trained DLS system might represent a trusted tool for the segmentation and detection of CMB lesions.